IMPLEMENTASI POLA DEFENCE DALAM PERMAINAN SEPAK BOLA BAGI ATLET USIA 11-15 TAHUN - Ritiauw, Petra Pratama; Rumawatine, Ztella; Somarwain, Falerius (German für Gesellschaft (J-Gefüge), 2024)
Football is a team game although individual skills can be used for a certain moment. In every way, the success of the team depends on the players working in combination. To control the ball and create scoring opportunities, team members must improve their ability to pass and receive the ball well, dribbling the ball to shoot the ball into the opponent's goal to score a goal. These abilities complement each other because each ball passed must be received and controlled by a teammate. Defense is an effort where players find a strategic place to defend in stopping the opponent's attack in a football game. Scheunemann (in Prasetyo, Dwiyogo, & Sudjana, 2016) mentioned the principles of defense, namely (a) Retreat between the ball and one's own goal, (b) Compactness, (c) Forechecking (pressing in the opponent's defensive area), (d) Midfield pressing (pressing in the midfield) (e) Fall back (pressing carried out in their own defensive area). Each team has a different strategy pattern. Before starting the training, the coach must explain the formation and position in detail.